2015
DOI: 10.1152/ajpgi.00081.2015
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ethanol consumption disrupts diurnal rhythms of hepatic glycogen metabolism in mice

Abstract: Chronic ethanol consumption has been shown to significantly decrease hepatic glycogen content; however, the mechanisms responsible for this adverse metabolic effect are unknown. In this study, we examined the impact chronic ethanol consumption has on time-of-day-dependent oscillations (rhythms) in glycogen metabolism processes in the liver. For this, male C57BL/6J mice were fed either a control or ethanol-containing liquid diet for 5 wk, and livers were collected every 4 h for 24 h and analyzed for changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 53 publications
4
26
0
Order By: Relevance
“…Glycogen levels vary in a daily fashion, but in ad-lib-fed mice, they only contribute about 4% and 6.5% to liver weight at trough and peak levels, respectively (Udoh et al, 2015). Therefore, they cannot account for the 34% difference in liver mass reported above.…”
Section: Resultsmentioning
confidence: 99%
“…Glycogen levels vary in a daily fashion, but in ad-lib-fed mice, they only contribute about 4% and 6.5% to liver weight at trough and peak levels, respectively (Udoh et al, 2015). Therefore, they cannot account for the 34% difference in liver mass reported above.…”
Section: Resultsmentioning
confidence: 99%
“…This desynchronization can mediate alcohol’s effects on hepatic lipid, glycogen, and mitochondrial metabolism. Her findings suggest a regulatory role for the liver clock on alcohol-induced liver injury and glycogen depletion 15 . In a hepatocyte-specific BMAL1 knockout mouse model for alcoholic fatty liver disease, failures in clock-driven metabolic adaptive processes in the alcohol-exposed liver mediated alcohol-induced hepatic bioenergetic stress and liver injury.…”
Section: Clock and Livermentioning
confidence: 98%
“…Changes in the alcohol metabolic pathway were observed in a Drosophila Per mutant, resulting in differences in alcohol tolerance and clearance capability64. On the other hand, long-term alcohol intake in mice can lead to changes in the circadian rhythm65, whilst damaging the normal rhythm of liver glycogen metabolism66. Numerous studies have reported such reciprocal regulation of the circadian clock by metabolites, whereby the metabolites regulate expression of core circadian clock genes, thus changing the circadian rhythm.…”
Section: Discussionmentioning
confidence: 99%